The right word at the right time a guide to the english language and how to use it - Kahn,John Ellison (Reader's Digest Association Limited, 1985)
This sequel to "Big Book of Time" deals with the concept of spaces, of every size, shape and description. Young readers will learn how big the biggest space is, how to measure and map the space around them, and how to see space too far away - or too tiny - for the naked eye to detect.